The training of the Physical Education teacher in Special Educational Needs, towards reflection and action, from international agreements and Laws in Chile - Castillo Paredes, Antonio Jonathan. (Federación Espanola de Docentes de Educación Física, 2021)
TheWarnock Report and the Salamanca Declaration established standardized criteria on concepts and minimum requirements for a homogeneous teaching of educational centers for people with Special Educational Needs (SEN). SEN within the regulations in Chile are classified as Permanent andTransitory Special Educational Needs.Which, through decrees, laws and international agreements, children and adolescents have the right to a quality education,taking into consideration the characteristics that students may present, this accompaniment may be transitory and / or permanent. In this way, it is sought that, through Special Education, students obtain the necessary tools for their use in social and work contexts. However, from Physical Education in school contexts, little preparation, or knowledge of the characteristics of SEN presented by a student is evidenced by the Physical Education teacher, although, in different universities there is the subject that provides students pedagogy of tools and competencies for working with schoolchildren with SEN, it is evident that there is a lack of theoretical and practical components to work with SEN. Finally, reflection is invited for the use of adapted physical - sports or motor activities, which could allow them to be a complementary and inclusive tool in the school Physical Education class.
La formación del profesor de Educación Física en las Necesidades Educativas Especiales, hacia la reflexión y la acción, desde acuerdos internacionales y Leyes en Chile
Keywords: Special educational needs.; Physical education.; Curriculum adaptations.; School.; University.; Disabled persons.